Dynamical Behaviour of Asteroids in the Region a < 2 AU - Lopez Garcia, Francisco (2001)
We carried out a series of numerical simulations of the dynamical evolution of test particles and real asteroids in the inner region of the Solar System. We explored two different scenarios: i) including terrestrial planets plus Jupiter and Saturn and ii) including all the planets (except Pluto). We found that there are possible zones of orbital stability where planetesimals may survive 100 Myr. Secular resonances with the inner planets and mean motion commensurabilities with both the inner and outer planets play a key role in the dynamical evolution of this region.